Pengaruh Manajemen SDM Strategik dan Kepuasan Kerja terhadap Kinerja Karyawan PT SBA Aceh Besar (International Forum of Researchers and Lecturers, 2025)
Integration between strategic human resource management practices and job satisfaction is an important factor that cannot be ignored. Organizations need to ensure that the HR management strategies implemented are not only oriented towards results, but also pay attention to the welfare and positive perceptions of employees towards their work. This study aims to analyze the effect of strategic human resource management practices and job satisfaction on employee performance at PT. Solusi Bangun Andalas in Aceh Besar. The research method used is quantitative. A sample of 150 permanent employees was taken using the Probability sampling technique. Data analysis was carried out using multiple linear regression and partial tests using IBM SPSS Statistics 25. The results showed that this study supports the proposed hypothesis, namely that strategic human resource management practices and job satisfaction have a significant positive effect on employee performance. Suggestions for PT. Solusi Bangun Andalas need to continue to strengthen strategic HR practices, including training, competency-based recruitment, and KPI-based performance evaluation. Job satisfaction must also be optimized through fair compensation, a positive work environment, and good communication. Integration between HR strategies and job satisfaction is important to be carried out synergistically in order to create a productive and sustainable HR system.